What if the officer were black or female?: the effects of officer race and gender on arrest decision-making - Mbuba, Jospeter M. (African journal of criminology and justice studies, 2018)
Race and gender in arrest decisions are some of the most enduring areas of study in policing, but the same cannot be said of research on the effect of officers’ race and gender on arrest decisions, which warrants more vigorous attention than it currently receives. Using a complete count of 136,160 arrests conducted over a period of eight years in a Midwestern city in the United States and a two-model approach, this study is intended to explain the effects of the race and gender of officers on who is arrested. Focusing on the role of conventional perceptions as well as the latent effect of police deployment practices, this study found that officers are generally more inclined to arrest members of their own racial groups, and that, holding racial backgrounds constant, female officers are more inclined than male officers to arrest racial-minority suspects, especially African Americans. The study further found that if all other factors are equal, then female officers over-arrest female suspects and male officers over-arrest male suspects. Other findings are presented, possible analytic explanations offered, and policy implications discussed. The study ends with a set of recommendations that are linked to the findings.